IMMEDIATE RESULT OF ICON INFILTRATION IN WHITE SPOT LESIONS CAUSED BY FLUOROSIS: A CASE REPORT - Al-Sadi Abdulaziz Nasser Zain; P.M. Skrypnykov; V.I. Shynkevych; O.A. Pysarenko (Український стоматологічний альманах, 2022)
The Icon technique is designed to effectively restore non-cavitary lesions (porosity in deor hypomineralized enamel). Infiltration of the composite resin increases the strength of demineralized enamel. The results of clinical application indicate the effectiveness of the Icon infiltration method in combination with microabrasion and professional whitening, as well as an excellent aesthetic effect for 2 years after treatment.